Use of tissue-specific microRNA to control pathology of wild-type adenovirus without attenuation of its ability to kill cancer cells. - Cawood, R; Chen, H; Carroll, F; Bazan-Peregrino, M; van Rooijen, N; Seymour, L (2009)
Replicating viruses have broad applications in biomedicine, notably in cancer virotherapy and in the design of attenuated vaccines; however, uncontrolled virus replication in vulnerable tissues can give pathology and often restricts the use of potent strains. Increased knowledge of tissue-selective microRNA expression now affords the possibility of engineering replicating viruses that are attenuated at the RNA level in sites of potential pathology, but retain wild-type replication activity at sites not expressing the relevant microRNA. To assess the usefulness of this approach for the DNA virus adenovirus, we have engineered a hepatocyte-safe wild-type adenovirus 5 (Ad5), which normally mediates significant toxicity and is potentially lethal in mice. To do this, we have included binding sites for hepatocyte-selective microRNA mir-122 within the 3' UTR of the E1A transcription cassette. Imaging versions of these viruses, produced by fusing E1A with luciferase, showed that inclusion of mir-122 binding sites caused up to 80-fold decreased hepatic expression of E1A following intravenous delivery to mice. Animals administered a ten-times lethal dose of wild-type Ad5 (5x10(10) viral particles/mouse) showed substantial hepatic genome replication and extensive liver pathology, while inclusion of 4 microRNA binding sites decreased replication 50-fold and virtually abrogated liver toxicity. This modified wild-type virus retained full activity within cancer cells and provided a potent, liver-safe oncolytic virus. In addition to providing many potent new viruses for cancer virotherapy, microRNA control of virus replication should provide a new strategy for designing safe attenuated vaccines applied across a broad range of viral diseases.